Gauge theoretic approach to (ordinary) gravity and its fuzzy extensions in three and four dimensions - Manolakos, George; Manousselis, P.; Roumelioti, D.; Stefas, S.; Zoupanos, George (Journal of physics. A, Mathematical and theoretical, 2022)
In the prospect to discuss the construction of fuzzy gravity theories based on the gauge-theoretic approach of ordinary gravity, in the present article we review first the latter in three and four dimensions and then, after recalling the formulation of gauge theories on noncommutative spaces, we present in detail the construction of fuzzy gravity theories in three and four dimensions, as matrix models.